A Novel Method of Isolating Myofibrils From Primary Cardiomyocyte Culture Suitable for Myofibril Mechanical Study - Woulfe, Kathleen C.; Ferrara, Claudia; Pioner, Jose Manuel; Mahaffey, Jennifer H.; Coppini, Raffaele; Scellini, Beatrice; Ferrantini, Cecilia; Piroddi, Nicoletta; Tesi, Chiari; Poggesi, Corrado; Jeong, Mark (Frontiers in Cardiovascular Medicine, 2019)
Myofibril based mechanical studies allow evaluation of sarcomeric protein function. We describe a novel method of obtaining myofibrils from primary cardiomyocyte culture. Adult rat ventricular myocytes (ARVMs) were obtained by enzymatic digestion and maintained in serum free condition. ARVMs were homogenized in relaxing solution (pCa 9.0) with 20% sucrose, and myofibril suspension was made. Myofibrils were Ca2+-activated and relaxed at 15°C. Results from ARVM myofibrils were compared to myofibrils obtained from ventricular tissue skinned with Triton X-100. At maximal Ca2+-activation (pCa 4.5) myofibril mechanical parameters from ARVMs were 6.8 ± 0.9 mN/mm2 (resting tension), 146.8 ± 13.8 mN/mm2 (maximal active tension, P0), 5.4 ± 0.22 s−1 (rate of force activation), 53.4 ± 4.4 ms (linear relaxation duration), 0.69 ± 0.36 s−1 (linear relaxation rate), and 10.8 ± 1.3 s−1 (exponential relaxation rate). Force-pCa curves were constructed from Triton skinned tissue, ARVM culture day 1, and ARVM culture day 3 myofibrils, and pCa50 were 5.79 ± 0.01, 5.69 ± 0.01, and 5.71 ± 0.01, respectively. Mechanical parameters from myofibrils isolated from ARVMs treated with phenylephrine were compared to myofibrils isolated from time-matched non-treated ARVMs. Phenylephrine treatment did not change the kinetics of activation or relaxation but decreased the pCa50 to 5.56 ± 0.03 (vehicle treated control: 5.67 ± 0.03). For determination of protein expression and post-translational modifications, myofibril slurry was re-suspended and resolved for immunoblotting and protein staining. Troponin I phosphorylation was significantly increased at serine 23/24 in phenylephrine treated group. Myofibrils obtained from ARVMs are a viable method to study myofibril mechanics. Phenylephrine treatment led to significant decrease in Ca2+-sensitivity that is due to increased phosphorylation of TnI at serine 23/24. This culture based approach to obtaining myofibrils will allow pharmacological and genetic manipulation of the cardiomyocytes to correlate biochemical and biophysical properties.